Elisha Swift report - Swift, Elisha
Handwritten fragment of a report by Swift and others concerning Connecticut settlers in Pennsylvania.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Migration, Internal -- United States; Connecticut -- History -- Colonial period, ca. 1600-1775.; Pennsylvania -- History -- Colonial period, ca. 1600-1775.